2014
DOI: 10.1016/j.ssi.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature synthesis of Al-doped Li7La3Zr2O12 solid electrolyte by a sol–gel process

Abstract: Al-doped Li7La3Zr2O12 (LLZ) was prepared by a sol-gel process using lithium nitrate, lanthanum nitrate hexahydrate, zirconium propoxide and aluminum tri sec-butoxide as starting materials. Single phase of cubic LLZ was obtained by a heat treatment at 700 o C, which is lower than that in the solid state reaction process. The LLZ powders were sintered at 900°C using LiBO2 or Li3BO3 to form composite solid electrolyte. In the composite sintered with LiBO2, La2Zr2O7 was formed as an impurity phase. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 23 publications
5
42
0
Order By: Relevance
“…More recently, additives of sintering as LiBO 2 , Li 3 BO 3 , Li 3 PO 4 , and Li 4 SiO 4 have shown positive effects for reducing the sintering temperature and maintaining high conductivity [14,[17][18][19]. Tadanaga and a coworker reported Li-ion conductivity of 1 × 10 −4 S cm −1 at 30°C using Li 3 BO 3 as an additive to pristine LLZO-Al, prepared at the lower sintering temperature of 900°C [14].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, additives of sintering as LiBO 2 , Li 3 BO 3 , Li 3 PO 4 , and Li 4 SiO 4 have shown positive effects for reducing the sintering temperature and maintaining high conductivity [14,[17][18][19]. Tadanaga and a coworker reported Li-ion conductivity of 1 × 10 −4 S cm −1 at 30°C using Li 3 BO 3 as an additive to pristine LLZO-Al, prepared at the lower sintering temperature of 900°C [14].…”
Section: Introductionmentioning
confidence: 99%
“…11 Attempts have also been made to reduce the sintering temperature and improve the control of stoichiometry via wet chemical synthesis as well as through additives acting as sintering aids. [12][13][14][15][16][17][18] It has been shown that Al migrates from the alumina crucible used for garnet synthesis, causing significant effects in the material including stabilization of the cubic phase. [15][16][17][18] Lithium salts such as Li 2 20 They also found that the glassy-like phase formed at the grain-boundaries increases the density of material as well as helps to decrease the grain-boundary and improve the total Li + conductivity.…”
mentioning
confidence: 99%
“…LLZ was prepared by a sol-gel process using LiNO 3 (Wako, Japan), La(NO 3 ) 3 ·6H 2 O (Wako, Japan), Zr(O-n-C 3 H 7 ) 4 (Sigma-Aldrich), Al(Osec-C 4 H 9 ) 3 , as starting materials [14,15]. CH 3 COCH 2 COOC 2 H 5 (EAcAc) was used as a stabilizing agent for the alkoxides.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have reported that LLZ was prepared at a lower temperature of 900°C by the sol-gel method [14,15]. High lithium ion conductive composite electrolyte with LLZ and amorphous Li 3 BO 3 was prepared from sol-gel derived precursor powders of LLZ and Li 3 BO 3 .…”
Section: Introductionmentioning
confidence: 99%